Improved oxidation resistance of 15 wt.% Cr ferritic stainless steels containing 0.08–2.45 wt.% Al at 1000 °C in air. (November 2015) - Xu, Yulai; Zhang, Xin; Fan, Lijun; Li, Jun; Yu, Xiaojiang; Xiao, Xueshan; Jiang, Laizhu
Graphical abstract: Highlights: Al improved oxidation resistance of 15Cr ferritic stainless steels at 1000 °C in air. Surface oxide scale evolves from ridge to needle-like and smooth morphology. Diffusion of Cr 3+ makes appearance of porous region and many oxide layers. Porous Cr2 O3 rich outer layer is replaced by a more compact Al2 O3 rich outer layer. Mechanism based on microstructure and chemical composition has been suggested. Abstract: Improved oxidation resistance of 15 wt.% Cr ferritic stainless steels at 1000 °C in air has been obtained. Weight gain per unit area is in parabolic relation to oxidation time and parabolic rate constant significantly decreases with increased Al content. Diffusion of Al is enhanced and the porous Cr2 O3 rich outer layer is replaced by a more compact Al2 O3 rich outer layer in steels with higher Al contents. The appearance of continuous and compact Al2 O3 oxide scale contributes to the significantly improved oxidation resistance property and the oxidation mechanism has been suggested based on microstructural observations.